An Explorative Study on The Role of Local Creativity-Based Coffee Tourism On Community Income In Sidikalang District - Christi Natalia Simarmata; Dearlina Sinaga; Nova Yunita Sari (CV Putra Publisher, 2026)
This study aims to analyze the role of coffee tourism based on local creativity in increasing community income in Sidikalang District. Sidikalang coffee, as a flagship commodity, has great potential as a tourist attraction, but has not yet been fully utilized. This study employs a qualitative method with an exploratory approach through interviews, observations, and documentation involving coffee farmers, MSME operators, government officials, and the community. Data analysis utilizes the SWOT framework to identify strengths, weaknesses, opportunities, and threats. The results indicate the presence of local creativity in coffee processing, presentation, and derivative products that can be developed into educational tourism and the creative economy, thereby contributing to increased community income. However, development remains constrained by limitations in promotion, facilities, and management. Therefore, a collaborative strategy between the community, business actors, and the government is needed to support the development of sustainable coffee